The Influence of Cell Geometry on the Behaviour of Composite Cellular Beams - Lane, Percy V. (My University, 1964)
Two types of tests are reported in this thesis: (1) tests of push -out specimens and (2) tests of composite cellular T -beams. The components of the composite members tested were short lengths of steel I -beams and concrete ribbed slabs. The ribbed slabs were formed by the inclusion of cellular sheet steel decking. Various rib sizes were used by varying the cell height and cell width of the decking. The components of a specimen were tied together by stud shear connectors. The tests were made to investigate the influence of cell geometry on the behaviour of composite cellular members and to provide a rational approach to their design.
Keywords: cell geometry; Cellular beams; cell behaviour